Social Cohesion of Local Wisdom for Plural Communities - Alis Asikin (International Journal Ihya' 'Ulum al-Din, 2021)
Local culture and traditions represent local wisdom. Values applied in society. These values are believed to be accurate and become references in their daily behavior.  The values of local knowledge are considered influential factors in determining the status and dignity of humans in their communities.  Because these values contain intelligence, creativity, and local wisdom from their ancestors, figures, and society.  The value of local wisdom that remains in our community is the nyadran ritual tradition.  Nyadran is considered a socio-religious and socio-cultural reflection even as a social, cultural, and religious transformation.  Nyadran is an expression of social piety where cooperation, solidarity, and togetherness are the main patterns of this tradition. The tradition in Jetis hamlet is in many ways able to develop primordial bonds in a cluster with the same beliefs and views despite different religions and beliefs.  This research includes qualitative-exploratory research that requires qualitative data.  As a case study, this research uses an ethnographic study approach, which is a tool for analyzing local wisdom whose data sources come from informants.